Contribution of Particulate and Mineral-Associated Organic Matter to Potential Denitrification of Agricultural Soils - Surey, Ronny; Kaiser, Klaus; Schimpf, Corinna M.; Mueller, Carsten W.; Böttcher, Jürgen; Mikutta, Robert (Frontiers in Environmental Science, 2021)
Water-extractable organic carbon (WEOC) is considered as most important carbon (C) source for denitrifying organisms but the contribution of individual organic matter (OM) fractions (i.e., particulate − POM and mineral-associated − MOM) to its release, and thus, to denitrification remains unresolved. Here we tested short-time effects of POM and MOM on potential denitrification and estimated the contribution of POM- and MOM-derived WEOC to denitrification and CO2 production of three agricultural topsoils. Suspensions of bulk soils with and without addition of soil-derived POM or MOM were incubated for 24 hours under anoxic conditions. Acetylene inhibition was used to determine the potential denitrification and respective product ratio at constant nitrate supply. Normalized to added OC, effects of POM on CO2 production, total denitrification, and its product ratios were much stronger than those of MOM. While the addition of OM generally increased the (N2O+N2)-N/CO2-C ratio, the N2O/(N2O+N2) ratio changed differently depending on the soil. Gas emissions and the respective shares of initial WEOC were then used to estimate the contribution of POM- and MOM-derived WEOC to total CO2, N2O, and N2O+N2 production. Water-extractable OC derived from POM accounted for 53 to 85% of total denitrification and WEOC released from MOM accounted for 15 to 47%. Total gas emissions from bulk soils were partly over- or underestimated, mainly due to non-proportional responses of denitrification to the addition individual OM fractions. Our findings emphasize that MOM also serves as C source during denitrification, although less strong than plant residues. We conclude that the denitrification potential of soils is not predictable based on the C distribution over POM and MOM alone. Instead, the source strength of POM and MOM for WEOC plus the WEOC’s quality turned out as the likely crucial determinants of potential denitrification.